RECENT TRENDS OF CRM PRACTICES IN NATIONALISED BANKS WITH SPECIAL REFERENCE TO COIMBATORE CITY - V, Nagarathinam; S., Murugan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s competitive banking environment, Customer Relationship Management (CRM) has become essential for nationalised banks striving to enhance customer satisfaction and loyalty, especially in urban areas like Coimbatore City. This study aims to explore recent trends in CRM practices within nationalised banks, with a focus on assessing their effectiveness in improving customer service utilization and satisfaction. The problem addressed is the need for nationalised banks to adapt CRM strategies that meet customer expectations and maintain loyalty amid growing competition from private and digital banks. The research objectives are to analyze the effectiveness of CRM strategies in enhancing service utilization and to assess their impact on customer satisfaction in Coimbatore. A Descriptive Research Design was employed, and data was collected from a sample of 134 respondents using Convenience Sampling. The study uses statistical tools such as ANOVA, Correlation Analysis, and Multiple Linear Regression to examine relationships among CRM strategies, service utilization, and customer satisfaction. Key findings reveal that digital banking tools, personalization, and user-friendly interfaces are highly valued by younger customers. Moreover, locality and educational level significantly influence CRM effectiveness, highlighting the need for location-specific strategies. Recommendations include enhancing digital banking platforms, expanding ATM networks, and investing in customer service training to improve conflict resolution. In conclusion, effective CRM strategies are essential for boosting customer satisfaction and fostering loyalty, underscoring the importance of continual adaptation and innovation in nationalised banks’ CRM practices to meet evolving customer needs in Coimbatore City.